Combination of Ursodeoxycholic Acid and Glutathione Improves Intestinal Morphology in Cholestasis by Downregulating TNF-α Expression - Jonathan Alvin Nugraha Halim; Endang Sri Lestari; Sigit Adi Prasetyo; Muflihatul Muniroh; Agung Aji Prasetyo (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: Cholestasis caused by obstruction of the common bile duct and may developed gut-derived sepsis due to reactive oxygen species (ROS) accumulation. Ursodeoxycholic acid (UDCA) and glutathione are widely known for their antioxidant properties, that might be beneficial against ROS. However, the effects of UDCA-glutathione combination against ROS have not been well elucidated in previous studies. Thus, this study was conducted to evaluate tumor necrosis factor (TNF)-α level and height of terminal ileal mucosal villus after UDCA-glutathione administration in cholestasis rat model.METHODS: Twenty-eight male Sprague Dawley rats were randomly grouped into four treatment groups, each group consisted of seven rats that had previously undergone bile duct ligation. Three groups received treatment of UDCA-glutathione combination on stratified dose, while the other one only received UDCA. Each treatment was given for 21 days. Ileal samples were collected from the rats and stained with mouse anti TNF-a antibody and hematoxylin-eosin (HE). Immunohistochemistry and histopathological examination were done using microscope and then calculated with ImageJ.RESULTS: The combination of UDCA and glutathione treatment decreased the TNF-α expression (p<0.05) compared to UDCA only group, particularly in group that received 20 mg UDCA and 15 mg glutathione supplementation (p<0.05) and group that received 30 mg UDCA and 20 mg glutathione supplementation (p<0.05). The height of the mucosa villous was higher in the UDCA-glutathione combination groups for all the three dosage variations given (p<0.05) compared to UDCA only group.CONCLUSION: UDCA-glutathione combination downregulates TNF-α expression and improves ileum mucosal villus height in cholestasis.KEYWORDS: cholestasis, glutathione, intestinal villus height, TNF-α, UDCA